US food allergy patients’ experiences, priorities, and needs: A qualitative study - Elisabeth Oehrlein, MS, PhD; Silke C. Schoch, MA; Omar A. Escontrías, DrPH, MPH; Melanie Carver, AS; Sanaz Eftekhari, BA; Jessica Marvel, MPH; Chris Leo Pashos, PhD; Michael Pistiner, MD, MMSc; Randall Rutta, MA; Jill Voss, BSc Hons, MSc; Joe Vandigo, MBA, PhD (Journal of Allergy and Clinical Immunology: Global, 2025)
Background: Understanding patient experiences with food allergies (FAs) is essential for developing treatments that meet patients’ needs and aiding clinicians in optimizing care. Objective: We sought to provide clinicians and researchers with an inclusive view of IgE-mediated FA patients’ experiences, including (1) FA’s natural history, including signs, symptoms, health system experiences, and diagnosis pathways; (2) the disease’s burden and psychosocial impacts on individuals and families; (3) perspectives on treatment attributes, benefits, and clinical trial participation; and (4) topics and resources patients and caregivers seek regarding FAs. Enhanced understanding of these challenges and opportunities can improve personalized care and patient outcomes. Methods: We conducted virtual interviews with 81 US residents with at least 1 physician-confirmed IgE-mediated FA. Interviews lasted up to 60 minutes. All participants were required to self-report a history of severe allergic reactions. Recruitment was via social media, health care providers, and patient advocacy organizations. Results: Most participants had multiple FAs, with peanuts and/or tree nuts (86%) being the most common. Common reaction types were skin/mouth (91%), respiratory (65%), and gastrointestinal (53%). Key diagnosis pathways included seeking urgent/emergency care after severe reactions and discussing moderate symptoms with primary care doctors. Barriers to diagnosis included long allergist wait times, travel, and other commitments. Most participants with epinephrine autoinjectors felt confident using them due to prior training. FA impacts varied, from minor daily disruptions to significant emotional, social, educational, and career challenges, mainly due to allergen avoidance efforts. Most participants (59%) showed an interest in clinical trials, influenced by potential risks and benefits, trial type, location, accessibility, and child willingness. Despite valuing epinephrine autoinjectors, participants noted unmet needs such as inconvenience, high costs, short expiration dates, and shortages. Desired treatment benefits included proactive treatments enabling allergen ingestion without symptoms and more information on FA management. Conclusions: This study offers insights into the diverse needs of IgE-mediated FA patients, highlighting the importance of comprehensive clinician awareness to enhance personalized care, optimize patient experiences, and improve outcomes. Addressing financial barriers and unmet needs through a team approach, clear communication, psychosocial support, and accessible resources is essential.